VIDEO ASSISTED THORACOSCOPIC RESECTION OF MEDIASTINAL ECTOPIC PARATHYROID GLANDS: A SINGLE-CENTER EXPERIENCE - Ristanovic, Aleksandar; Marić, Nebojša; Nikolic, Aleksandar; Čičić, Stevan (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: The majority of mediastinal ectopic parathyroid glands (MEPTG) can be successfully removed through the cervical approach, including parathyroid glands (PTG) located in the upper mediastinum. However, 1% – 3% of patients with hyperparathyroidism (HPT) require the thoracic surgical approach. The success of surgical treatment depends on the precise preoperative localization of MEPTGs and on the choice of the appropriate approach. In this group of patients, video assisted thoracoscopic excision of MEPTGs can be used as a reliable method, in order to avoid open surgery, but also because of its other advantages. We present the first 11 patients with MEPTGs who were successfully surgically treated at the Clinic for Cardiothoracic Surgery of the Military Medical Academy (MMA). Previous video assisted thoracoscopic resections in Serbia have not been reported. Materials and methods: Between March 2014 and October 2022, 11 patients with biochemically proven hyperparathyroidism were surgically treated at the Clinic for Cardiothoracic Surgery of the MMA. MEPTGs were identified preoperatively with a Tc-99m sestamibi scan, a CT scan of the chest, and single photon emission computed tomography (SPECT). Results: All MEPTGs were successfully excised using video assisted thoracoscopic surgery (VATS). There was no need for an open thoracic surgical approach (sternotomy or thoracotomy). The average length of the surgery was 80 minutes (between 34 and 150 minutes). The average length of hospitalization was 7 days. Postoperative wound infection occurred in one patient. Conclusion: MEPTGs can be safely and successfully excised using VATS, thus avoiding classical chest opening. VATS provides good visualization of the tumor, low tissue trauma, short duration of surgery and hospitalization, a low rate of complications, and a good cosmetic/aesthetic effect.